2017
DOI: 10.4081/aab.2017.6458
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnologically relevant features of gluconic acid production by acetic acid bacteria

Abstract: The many uses of gluconic acid and some of its salts are arousing increasing interest in these compounds and in their production levels. Although gluconic acid and gluconates can be obtained chemically, they are currently almost exclusively biotechnologically produced, mostly by fungus based methods. There is, however, an ongoing search for alternative microorganisms to avoid the problems of using fungi for this purpose and to improve the productivity of the process. Especially promising in this respect are ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Using G. oxydans 621H it was found that below pH 3.5 to 4 uptake and assimilation of GA into the PPP is almost completely inhibited (Olijve & Kok, ). This is likely to be related to the pH optima for the various enzymes involved in these processes–the periplasmic dehydrogenases involved in oxidative fermentation have pH optima in the acidic range of pH 3 to 6, while those cytoplasmic (NAD(P)‐dependent) dehydrogenases have optima in the alkaline range of pH 8 to 11 (García‐García et al., ). Therefore, the production of GA and associated pH drop may promote its own production and accumulation as the periplasmic dehydrogenases become more active.…”
Section: Biotechnological Applications Of G Oxydans Relevant To the mentioning
confidence: 99%
See 4 more Smart Citations
“…Using G. oxydans 621H it was found that below pH 3.5 to 4 uptake and assimilation of GA into the PPP is almost completely inhibited (Olijve & Kok, ). This is likely to be related to the pH optima for the various enzymes involved in these processes–the periplasmic dehydrogenases involved in oxidative fermentation have pH optima in the acidic range of pH 3 to 6, while those cytoplasmic (NAD(P)‐dependent) dehydrogenases have optima in the alkaline range of pH 8 to 11 (García‐García et al., ). Therefore, the production of GA and associated pH drop may promote its own production and accumulation as the periplasmic dehydrogenases become more active.…”
Section: Biotechnological Applications Of G Oxydans Relevant To the mentioning
confidence: 99%
“…Long lag phases were observed due to the combined effect of high glucose concentration and the low pH due to GA formation (Velizarov & Beschkov, , ). High glucose concentrations (approximately 90 g/L) also favored GA production over ketogluconate formation (Beschkov et al., ; García‐García et al., ).…”
Section: Biotechnological Applications Of G Oxydans Relevant To the mentioning
confidence: 99%
See 3 more Smart Citations